Produção de biomassa, óleo essencial e genotoxicidade de camomila (Chamomilla recutita) cultivada com soluções homeopáticas de phosphorus - Ubessi, Cassiane (2019)
Chamomile is one of the most cultivated medicinal plants in the Brazil due to its therapeutic properties present in flowers, from which the essential oil is extracted. The use of homeopathic medicines in the cultivation of medicinal plants promotes changes in plant metabolism that may influence productivity, secondary metabolism and, consequently, the use of plant derivatives. In this context, the objective of this study was to evaluate different dynamizations of the Phosphorus homeopathic medicines in the production of biomass and essential oil of chamomile, as well as the genotoxic effects of infusions and essential oil through the test of Allium cepa, and the effect on a nutritional restriction condition of the chemical element phosphorus. At the first moment, four Phosphorus dynamizations were evaluated: 3CH, 6CH, 12CH and 30CH, in the cultivar Mandirituba, with the treatments control distilled water and 70% alcohol. All variables related to the production of biomass, flowers, content, productivity and essential oil composition of chamomile were measured. The evaluation of genotoxicity by means of the Allium cepa test was conducted with two concentrations (10 and 40 g L-1) of inflorescences for the preparation of infusions and 0.10% (v v-1) diluted essential oil. The phenolic compounds were determined by liquid chromatography. In the second moment, only the 3CH dynamization of Phosphorus in the cultivation of chamomile with the restriction of the chemical element phosphorus was evaluated. All variables mentioned above were evaluated, except the genotoxicity test and the phenolic compounds. In the two moments the determination of the mineral composition present in the plant tissue of chamomile was carried out. The productivity of flowers per hectare can be increased with the application of the 30CH dynamization that raises the levels of nitrogen and iron in the plant tissue. The diameter and height of inflorescences increase with the use of 3CH dynamization, which is also efficient in raising the content and productivity of essential oil in chamomile, under optimum conditions of cultivation. Phosphorus cultivation does not induce a genotoxic effect in the use of infusions and essential oil of chamomile. The homeopathic medicine Phosphorus 3CH and the restriction of phosphorus did not promote increases in the content and productivity of essential oil and flowers in chamomile. However, the stress promoted by the restriction of phosphorus increased the concentration of the major analytes present in the essential oil. The homeopathic medicine Phosphorus gives effect on chamomile cultivation, with positive responses in increasing the productivity of flowers and essential oil, without toxic effect on products from this species. Phosphorus 30CH and 3CH can be used in plants that exhibit low flower production and essential oil, respectively, under favorable growing conditions. Under nutritional restriction, Phosphorus 3CH does not provide advantageous effects on chamomile cultivation and the stress promoted by phosphorus restriction increases the concentration of the major analytes present in the essential oil.